The Internalization of the Pesenggiri Pillar and Religious Moderation in Strengthening Student Character at SMA N 1 Way Jepara, East Lampung - Subandi; Muhammad Muchsin Afriyadi; Sela Kholidiani; Finny Ligery (CV. Creative Tugu Pena, 2024)
Character or morals in the global era play a dominant role, where students will always integrate with their surroundings. This study aims to examine the integration of the Piil Pesenggiri philosophy and religious moderation in strengthening the character of students at SMA N 1 Way Jepara, East Lampung. The Piil Pesenggiri philosophy, which is a local cultural heritage of the Lampung community, teaches values ​​such as self-respect, friendliness, mutual cooperation, and the importance of maintaining self-esteem and honesty. On the other hand, religious moderation plays an important role in forming attitudes of tolerance, inclusiveness, and respect for religious diversity in society. This study uses a qualitative approach with a phenomenological design, collecting data through interviews, observations, and documentation, data sources obtained from students and teachers, the validity of the data used triangulation techniques, analysis using display data, and interpretation, (Miles & Huberman). The results of the study indicate that the Piil Pesenggiri philosophy has been applied in subjects such as Pancasila Education, Indonesian Language, and extracurricular activities in schools. The religious moderation program is also implemented through activities such as interfaith discussions and joint celebrations of religious holidays. The majority of students feel that the integration of the two values ​​has succeeded in increasing attitudes of tolerance and strengthening positive character, such as empathy, respect for differences, and the ability to work together in diversity. The impacts produced by students have, the integration of Piil Pesenggiri values ​​and religious moderation can contribute to forming a young generation that is religious, tolerant, and cultured.